2022
DOI: 10.2147/copd.s355897
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship of Airflow Obstruction in COPD with Severity of OSA Among Patients with Overlap Syndrome

Abstract: Background Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) are common diseases affecting millions worldwide. These two diseases have a complex relationship that is not well understood. Previous small studies suggest an inverse relationship of disease severity of OSA with COPD airflow obstruction. Objective The aim of this study was to determine if a relationship exists between severity of airflow obstruction in COPD and severity of OSA via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In contrast, as expected, the comparison of the OS group to OSA-only patients showed significantly lower values of FEV 1 /FVC, FEV 1 , FVC%, peak expiratory flow, and SaO 2 in the first group [55,56,62]. However, the severity of COPD did not have an impact on the severity of OSA in patients with an OS diagnosis [27,38,84]. On the other hand, unrecognized and untreated OSA increased hospital readmissions in patients admitted for COPD exacerbation [24,34,[85][86][87], but treatment with continuous positive airway pressure (CPAP) in OS patients decreased the risk of COPD exacerbation to frequencies similar to those in COPD-only groups [14].…”
Section: Polysomnography Findings and Pulmonary Function In Overlap S...mentioning
confidence: 79%
“…In contrast, as expected, the comparison of the OS group to OSA-only patients showed significantly lower values of FEV 1 /FVC, FEV 1 , FVC%, peak expiratory flow, and SaO 2 in the first group [55,56,62]. However, the severity of COPD did not have an impact on the severity of OSA in patients with an OS diagnosis [27,38,84]. On the other hand, unrecognized and untreated OSA increased hospital readmissions in patients admitted for COPD exacerbation [24,34,[85][86][87], but treatment with continuous positive airway pressure (CPAP) in OS patients decreased the risk of COPD exacerbation to frequencies similar to those in COPD-only groups [14].…”
Section: Polysomnography Findings and Pulmonary Function In Overlap S...mentioning
confidence: 79%
“…However, a more recent study found a lack of relationship between the severity of airway obstruction and the severity of OSA [41].…”
Section: Discussionmentioning
confidence: 92%
“…OSA and COPD are among the most prevalent chronic diseases and represent a major economic burden for healthcare systems worldwide (6). The clinical presentation of OSA-COPD 'overlap syndrome' compared to OSA alone remains undefined and more research is needed to elucidate how the association of both diseases exercises an impact on cardiovascular (CV) health (7). The objective of this paper was to study the main differences between OSA in patients with OSA alone, compared to OSA and COPD and to OSA, COPD and obesity.…”
mentioning
confidence: 99%